Multi-image authentication, encryption and compression scheme based on double random phase encoding and compressive sensing - Xue, Linlin; Ai, Caihua; Ge, Zenghao (Physica scripta, 2025)
Images may be subject to malicious tampering during transmission, making image encryption technology critically important. However, it remains challenging for the receiver to verify whether the received image is correct. This paper introduces a multi-image authentication, encryption and compression scheme that combines double random phase encoding (DRPE) and compressive sensing (CS) to address this issue. First, a random sampling matrix is used to downsample multiple plaintext images separately, which are then combined into one composite sampled image. Next, DRPE is employed to encode the composite sampled image and generate authentication information. The authentication information extracted in this way contains information of all plaintext images, making it possible to batch authentication of multiple images. Simultaneously, based on the encryption-then-compression (ETC) framework, multiple plaintext images are encrypted, compressed and quantized, forming ciphertext images. Finally, the ciphertext images and the authentication information are embedded into a carrier image for transmission. At the receiver’s side, the ciphertext images and authentication data are extracted from the carrier image. After that, image reconstruction and decryption are performed on the ciphertext images, and the reconstructed images are authenticated using the decoded authentication information. Simulation results show that the proposed scheme can significantly enhance the authentication efficiency while reducing the authentication information, and it outperforms existing single-image and double-image authentication schemes regarding authentication quality.